Business Perceptions of Access Management Techniques. (January 2015) - Cunningham, Christopher M.; Katz, Donald; Smith, Sarah; Carter, Daniel; Miller, Mike; Findley, Daniel J.; Schroeder, Bastian; Foyle, Robert S.
Transportation agencies have made significant strides to reduce collisions and increase capacity along strategic highway corridors. Efforts have led to the implementation of many different access management techniques along corridors, such as installing medians versus two-way left-turn lanes and closing median openings. Businesses along these corridors have indicated their concern that these new designs will have a negative economic impact on their business because of the lack of direct access to their properties. The objective of this study was to quantify the business perceptions of median treatments on businesses adjacent to multilane highways. Owners of businesses along treatment corridors viewed median installations with a more positive outlook following implementation of the median than they did prior to the installation. The performance of treatment sites in terms of reported impacts on business revenues indicates that there is no direct evidence of negative economic impacts due to median installations.